AURICULAR PROSTHESIS OF SILICONE RUBBER - Nagayama, Ikuo (JIBI INKOKA TEMBO, 1988)
A case of auricular cancer is reported. The pationt is a 56-year-old female who has suffered from earache for one year and a half. Biopsy of the auricle revealed adenoid cystic carcinoma. Total auricular resection containing the tragus was performed, preserving external bone canal. The surgical defect was repaired with full thickness skin graft and split thickness skin graft. Right ear scalpture (made of dental rubber) served as a model of a prosthesis. This ear model was sent to Sato Giken (Kyoto) to make a auricular prosthesis. Silicone rubber prosthesis is attached to the defect using adhesive made of silicone. Silicone prosthesis showed a superior cosmetic result. Silicone rubber has excellent property in texture, color and softness.